Computational Methods in Low Impact Development Stormwater Control Measures - Barker, Bruce; Beyerlein, Douglas; Blake, Stephen; Burger, Caroline; Gregory, Mike; Moin, Sheida; Pitt, Robert; Rossman, Lewis A; Tangtrakul, Korin; Voorhees, John (American Society of Civil Engineers (ASCE), 2023)
Sponsored by the LID Computational Methods Task Committee of the Urban Water Resources Research Council of the Environmental and Water Resources Institute of ASCE. This book provides a summary of current low impact development (LID) computation methods. This particular report focuses on the approaches that address hydrologic or hydraulic processes such as runoff generation, infiltration, evapotranspiration, flow conveyance, and detention.Topics include: Literature review of hydrologic and hydraulic processes at work in LID systems, Overview of LID computational modeling, H&H (hydrologic and hydraulic) models, Capabilities of common modeling tools currently in use across the United States, and Case studies demonstrating the following models: MIKE+, WinSLAMM, PC SWMM, WWHM, MGS Flood. This publication will help civil engineers interested in LID stormwater control measures identify computational methods that may be the most relevant or useful to their specific use case.